1999
DOI: 10.1038/sj.bjc.6690232
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of Carzelesin (U-80,244) given (4-weekly) by intravenous bolus schedule

Abstract: Carzelesin is a cyclopropylpyrroloindole analogue which acts as a DNA-sequence-specific alkylating agent. In this phase I study, Carzelesin was given as a 4-weekly 10 min IV infusion to 51 patients with advanced solid tumours. Patients received a median of two courses (range 1–5) at one of nine dose levels: 24, 48, 96, 130, 150, 170, 210, 250 and 300 μg m −2 . According to NCI-CTC criteria, non-haematological toxicities (grade 1/2) included fever, nausea and vomiting, mucositis and anore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Subsequently analogs of CC-1065, including adozelesin, bizelesin, and carzelesin, were developed and have been evaluated in phase I-II clinical trials. [17][18][19][20][21][22][23][24][25] Hematologic toxicity, particularly neutropenia and thrombocytopenia, was dose limiting in the phase I trials. [18,19,21,22,24,25] The onset of hematologic toxicity tends to be delayed and prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently analogs of CC-1065, including adozelesin, bizelesin, and carzelesin, were developed and have been evaluated in phase I-II clinical trials. [17][18][19][20][21][22][23][24][25] Hematologic toxicity, particularly neutropenia and thrombocytopenia, was dose limiting in the phase I trials. [18,19,21,22,24,25] The onset of hematologic toxicity tends to be delayed and prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…[57] Prolonged recovery of neutrophil and platelet counts resulted in treatment delays. When given as a single IV bolus at doses of 130 μg/m 2 or above, this pattern of bone marrow suppression was observed in 26% of courses of chemotherapy.…”
Section: Clinical Studies Of Cpi Analoguesmentioning
confidence: 99%
“…Three patients with renal carcinoma have had prolonged disease stabilization (15, 9 and 6 months). No responses [57] IV bolus, 1 day q4w 51 53 (21-71)/1 (0-2) 24-300 μg/m 2 (9) Neutropenia; thrombocytopenia 9 SD 300 μg/m 2 150 μg/m 2 Bizelesin Pitot et al [60] IV bolus, 1 day q4w 15 66 ( have been observed to date. Toxicity has consisted of transient neutropenia with no neutropenic fever.…”
Section: Clinical Studies Of Cpi Analoguesmentioning
confidence: 99%